THE EFFECTIVENESS OF OUTBOUND MANAGEMENT TRAINING WITH GAME TECHNIQUE TO IMPROVE STUDENTS’ SELF-ADJUSTMENT - Asri, Dahlia Novarianing; Dewi, Noviyanti Kartika (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Students need to adjust because, as adult individuals, they must deal with the expectations and hardships of college life. One of the initiatives to promote personal mental health is self-adjustment. The inability to adapt to daily life in various social environments can cause unhappiness for someone, especially students. One effort to improve student adjustment is through outbound management training using game techniques. The aim of this research is to determine the effectiveness of outbound management training using game techniques to improve student adjustment. This research is quantitative research with a one-group pretest posttest research design. The research subjects were 12 students from the Guidance and Counseling Study Program at PGRI Madiun University. The sampling technique uses the purposive sampling technique. The data collection technique uses a self-adjustment scale consisting of 15 items referring to the Psychology of Adjustment theory, including four components, namely accurate perception of reality, ability to overcome stress and anxiety, positive self-image, ability to express feelings, and good interpersonal relationships. The data analysis technique uses the Wilcoxon signed rank test. The research results show that outbound management training is effective in improving students' adjustment to everyday life.